Array - Pratama, Alvian Arya (Paradigma, 2022)
Abstract This paper discusses the social construction of the plipir community regarding the practice of congregational Friday prayers during the pandemic. The Indonesian government has implemented various policies to minimize the spread of COVID-19, including carrying out Friday prayers, resulting in changes in religious traditions and religious behavior of the community in general. This study uses the theoretical concept of Peter L. Berger with three components, namely externalization, objectification and internalization. This study uses a qualitative method and uses a phenomenological approach with the aim of revealing a phenomenon of religious behavior that occurred in the plipir community during the covid-19 pandemic. The research location is in Sidoarjo District. The results of the research on this phenomenon are that prayers must be performed in accordance with the law and legal requirements as a form of externalization of the Prophet Muhammad SAW from the results of Allah's commands for humans, especially Muslim communities and then strongly internalized in people in the world, especially in the plipir community through the da'wah of the Prophet Muhammad SAW. to the Wali, Ulama, Al-Qur'an and Al-Hadith. The community carries out the objectivity of religious activities, especially in carrying out prayers in accordance with the rules, laws and conditions for valid prayers that have been stated in the Al-Qur'an and without changing anything, even during a pandemic. Keywords: Community, Congregational Prayer, Covid-19, Social Construction